ANALISIS RISK BASE CAPITAL (RBC) DI PERUSAHAAN ASURANSI - Bogar, Syahfebriano (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2016)
This research analyzes the influence of internal and external factors toward the Stability of insurance company based on Risk Base Capital Method with case study of PT Asuransi Jiwa Nusantara. Statistical methods applied in the recent study are regression analysis, solvency margin, minimum solvency margin, Balance level Investment In Liabilities, Net premiums Equalization Levels With Equity, Deposit Interest Rate, inflation rate, Economic growth, Population growth as independent variable while Health Insurance Company as dependent variable.Findings show that generally regression analysis, solvency margin, minimum solvency margin, Balance level Investment In Liabilities, Net premiums Equalization Levels With Equity, Deposit Interest Rate, inflation rate, Economic growth, Population growth have a significant impact on the Company's Health Insurance Net premiums while Equilibrium Level With Equity, Deposit Interest Rate, Economic Growth does not have a significant impact on the Company's Health Insurance But simultaneously Level Level Solvency, Solvency Level Limit Minimum Investment Balance Levels With Liabilities, Net premiums Equalization Levels With Equity, Deposit Interest Rate, Inflation, Economic Growth and Population growth has a significant influence on the Health Insurance Company.